2019
DOI: 10.1590/1981-22562019022.180163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional disability and associated factors in the elderly

Abstract: Objective: To estimate the prevalence and self-reported socio-demographic and health factors associated with functional disability in basic and instrumental activities of daily living among the elderly. Method: A cross-sectional study was carried out, based on a representative sample of elderly people receiving care at a reference unit in the north of the state of Minas Gerais. The data were collected in 2015. Demographic and socioeconomic variables, morbidity, hospitalizations in the previous year, frailty (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 22 publications
7
10
1
6
Order By: Relevance
“…In the present study, the highest prevalence rates of dependence in IADL were found among diabetic older adults aged 75+ and those with complete secondary education, income below two minimum wages, previous history of stroke, current peripheral neuropathy, heart failure and self-reported cognitive problems. These findings are strongly correlated with data found in Brazilian and international studies (Barbosa et al Aguiar et al (2019), education proved to be a means for individuals to become aware of the most diverse risk factors for diseases and unhealthy working conditions, which could lead to less exposure to situations that could predispose people to diseases in the future and which may lead to an imbalance in the various organic systems as they age. Furthermore, education has proved to be a positive factor for strengthening psychosocial and behavioral aspects (Pereira et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, the highest prevalence rates of dependence in IADL were found among diabetic older adults aged 75+ and those with complete secondary education, income below two minimum wages, previous history of stroke, current peripheral neuropathy, heart failure and self-reported cognitive problems. These findings are strongly correlated with data found in Brazilian and international studies (Barbosa et al Aguiar et al (2019), education proved to be a means for individuals to become aware of the most diverse risk factors for diseases and unhealthy working conditions, which could lead to less exposure to situations that could predispose people to diseases in the future and which may lead to an imbalance in the various organic systems as they age. Furthermore, education has proved to be a positive factor for strengthening psychosocial and behavioral aspects (Pereira et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…The researchers argued that in IADL people will directly depend on the environment in which they are inserted, that is, their interaction outside the home will depend on what is offered in the environment, such as quality sidewalks, accessibility in public places, green areas and leisure areas, among others (Danielewicz et al, 2019). These findings are similar to those found in other studies (Aguiar et al, 2019;Ramos et al, 2017). On the other hand, a Canadian study found an association between household income and prevalence of older adults with impaired functional capacity, but the pathway by which these variables correlate requires further research (Philibert et al, 2013).…”
Section: Discussionsupporting
confidence: 66%
“…With regard to the instrumental activities, the dependence associated with the frailty syndrome was verified in national ( 34 - 37 ) and international studies ( 38 ) . Considered as public health problems, the frailty syndrome and functional dependence represent a challenge for societies in general, as they have a negative impact on the health and quality of life of the aged population ( 36 ) .…”
Section: Discussionmentioning
confidence: 98%
“…35 Associations between functional dependence for IADL 8-10 and AADL, 6,7,10 and illiteracy were also observed in previous studies with the community-dwelling elderly population. [6][7][8][9][10] Activities related to social participation generally require greater cognitive skills and technological devices; 36,37 therefore, low schooling can cause increased vulnerability in the performance of such activities. 8,9 Still, lack of schooling constitutes an unfavorable social condition.…”
Section: Ourmentioning
confidence: 99%